Hak Moral pada Cover Musik dalam Platform Digital Berdasarkan Hukum Positif Indonesia - Wisantoro Nusada Wibawanto; Tasya Safiranita; Rika Ratna Permata (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The level of use of the internet and digital platforms in Indonesia is quite even, making it easy to find various content on the internet. YouTube is a digital platform that is commonly used by the public to upload their creativity. These uploads can have a positive or negative impact in the form of violations. This study uses normative juridical research methods with descriptive research specifications. Based on the results of this study, it was found that music covers can be categorized as violations of moral rights within certain limits, such as changing lyrics without permission. The responsibility of digital platforms is also limited through the Safe Harbor Doctrine, namely as long as electronic system operators have carried out their obligations in providing a system that is safe, reliable and in accordance with laws and regulations, the digital platform can be free from responsibility for violations that occur on its platform.